The Second International Asteroid Warning Network Timing Campaign: 2005 LW3 - Davide Farnocchia; Vishnu Reddy; James M. Bauer; Elizabeth M. Warner; Marco Micheli; Matthew J. Payne; Tony Farnham; Michael S. Kelley; Miguel R. Alarcon; Paolo Bacci; Roberto Bacci; Mauro Bachini; et al. (The Planetary Science Journal, 2023)
The Earth close approach of near-Earth asteroid 2005 LW3 on 2022 November 23 represented a good opportunity for a second observing campaign to test the timing accuracy of astrometric observation. With 82 participating stations, the International Asteroid Warning Network collected 1046 observations of 2005 LW3 around the time of the close approach. Compared to the previous timing campaign targeting 2019 XS, some individual observers were able to significantly improve the accuracy of their reported observation times. In particular, U.S. surveys achieved good timing performance. However, no broad, systematic improvement was achieved compared to the previous campaign, with an overall negative bias persisting among the different observers. The calibration of observing times and the mitigation of timing errors should be important future considerations for observers and orbit computers, respectively.